Optimal contests with incomplete information and convex effort costs - Mengxi Zhang (Theoretical Economics, 2024)
I investigate the design of effort-maximizing mechanisms when agents have both private information and convex effort costs, and the designer has a fixed prize budget. I first demonstrate that it is always optimal for the designer to utilize a contest with as many participants as possible. Further, I identify a necessary and sufficient condition for the winner-takes-all prize structure to be optimal. When this condition fails, the designer may prefer to award multiple prizes of descending sizes. I also provide a characterization of the optimal prize allocation rule for this case. Finally, I illustrate how the optimal prize distribution evolves as the contest size grows.
Keywords: D44; D82; 330; incomplete information; mechanism design; Optimal contest